Developing Green Entrepreneurship Based on the Green Economy: Analysis of Foreign Experience (KIUT Publication, 2025)
This article examines the development of small businesses and private entrepreneurship based on the concept of the green economy, exploring the advantages of entrepreneurial activities within the green economy framework and analyzing international experiences. Based on the research findings, practical recommendations have been proposed for promoting green entrepreneurship in Uzbekistan.